Artisanal Business Scaling Pada Industri Kreatif Akar Jati Desa Kedungbenda Melalui Upaya Digital Branding dan Efisiensi Produksi - Famila Dwi Winati; Gladi Pawestri Utami; Diovianto Putra Rakhmadani (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2023)
Akar Wijaya is a creative industry with superior products in the form of artisan sculptures made from teak roots. In the marketing sector, Akar Wijaya's unpreparedness in utilizing digital technology for marketing and sales means that Akar Wijaya's exposure could be a lot higher. The inability to meet all demand in the production sector is also caused by the extended production time, namely 5-7 days per craft. Therefore, this program aims to increase Akar Wijaya's turnover by solving two main priority problems: implementing digitalization in the branding and marketing process and production efficiency by cutting machine technology to reduce production time. At the end of the program, UMKM Akar Wijaya had a visual identity in the form of a logo, which was then applied to the website to improve branding. In addition, digital branding training was carried out, which significantly increased participants' understanding. Implementation of production technology has the impact of reducing production time by up to 50%.